GAD65 Antibody Epitopes and Genetic Background in Latent Autoimmune Diabetes in Youth (LADY) - Peng, Yiman; Li, Xia; Xiang, Yufei; Yan, Xiang; Zhou, Houde; Tang, Xiaohan; Cheng, Jin; Niu, Xiaohong; Liu, Jing; Ji, Qiuhe; Ji, Linong; Huang, Gan; et al. (Frontiers in Immunology, 2022)
Epitope-specific GAD65Abs and HLA-DR-DQ gene assays help improve the value of risk stratification in autoimmune diabetes mellitus and protect islet function. Identification and early intervention are important for latent autoimmune diabetes in youth (LADY). The aims of this study were to investigate (1) the frequencies the epitope-specific GAD65Abs and HLA-DR-DQ genes in LADY and (2) the association between HLA-DR-DQ genes and epitope-specific GAD65Abs. Higher frequencies of GAD65-CAb and multiepitope GAD65Abs were observed in young type 1 diabetes, LADY and old type 1 diabetes subjects than in latent autoimmune diabetes in adults (LADA) patients. The frequencies of the specific susceptible HLA haplotype DR3, total susceptible HLA haplotypes and high-risk genotypes were higher in type 1 diabetes and LADY patients than in LADA patients. In contrast, type 1 diabetes and LADY patients had lower frequencies of low/no genetic risk genotypes (DRX/X) than that of LADA patients. Logistic regression analysis suggested that the susceptible HLA haplotypes were risk factors for GADA multiepitope positivity in autoimmune diabetes mellitus. LADY may be more severe than LADA, and LADY seemed to be a transitional type of type 1 diabetes and LADA. GADA epitope and HLA-DR-DQ gene assays are important for risk stratification in autoimmune diabetes mellitus and protection of islet function.